Introduction - Manzoli, Francesco Antonio; Toni, Roberto; Lechan, Ronald M.; Sandri, Giorgio; Vitale, Marco; Azzali, Giacomo (Acta Biomedica Atenei Parmensis, 2007)
This Special Issue of ActaBiomedica entitled “New Frontiers and Modelling in Neural, Endocrine and Immune Communication”, was conceived primarily to highlight some of the concepts presented during a series of symposia and lectures that took place at the University of Parma between March 2001 and October 2006...